Buying time with THRIVE. Issue 1 (24th April 2016) - Lion, Peter; Hodge, Elizabeth; Myatt, John G; Sandhu, Guri
Summary: We present the case of a 44‐year‐old male who was referred to our specialist benign airway disease service with epidermolysis bullosa acquisita causing supraglottic stenosis. He had previously had an attempted microlaryngoscopy at another institution, however this had been aborted due to failure to visualise the airway. Using Transnasal Humidified Rapid‐Insufflation Ventilatory Exchange (THRIVE) as a pre‐ and post‐induction oxygenation (and partial ventilation) tool to increase the apnoeic window, we were able to safely obtain a patent airway and treat the patient's disease. We suggest that THRIVE can be used in high risk airway patients to increase apnoeic windows in order to extend the time that may be needed to obtain a safe airway.